Aeromedical Battlefield Evacuation Under Endogenous Uncertainty in Casualty Delivery Times - Lejeune, Miguel A.; Margot, Francois (Management science, 2018)
We propose a new medical evacuation (MEDEVAC) model with endogenous uncertainty in the casualty delivery times. The goal is to provide timely evacuation and medical treatment to injured soldiers. The model enforces the “Golden Hour” evacuation doctrine, attempts to maximize the expected number of severely injured soldiers evacuated within one hour without delay, and represents the availability of air ambulances as an endogenous source of uncertainty. The MEDEVAC model is a mixed-integer nonlinear programming problem whose continuous relaxation is in general nonconvex and for which we develop an algorithmic method articulated around (i) new bounding techniques obtained through the solution of restriction and relaxation problems and (ii) a spatial branch-and-bound algorithm solving conic mixed-integer programs at each node. The computational study, based on data from Operation Enduring Freedom, reveals that the bounding problems can be quickly solved regardless of problem size, the bounds are tight, and the spatial branch-and-bound dominates the CPLEX and BARON solvers in terms of computational time and robustness. Compared to the MEDEVAC myopic policy, our approach increases the number of casualties treated timely and can contribute to reducing the number of deaths on the battlefield. The benefits increase as the MEDEVAC resources become tighter and the combats intensify. The model can be used at the strategic level to design an efficient MEDEVAC system and at the tactical level for intelligent tasking and dispatching. Data are available at https://doi.org/10.1287/mnsc.2017.2894 . This paper was accepted by Yinyu Ye, optimization.